COMPARATIVE CHARACTERISTICS OF EARLY MIOCENE VOLCANISM IN SAKHALIN ISLAND AND EARLY-MIDDLE MIOCENE VOLCANISM IN THE EASTERN SIKHOTE-ALIN: COMPARISON OF CHEMISTRIES - Shilov V.N. (My University, 1999)
According to the present day knowledge, the stratigraphic equivalents of the Early Miocene volcanic rocks of Sakhalin in the East Sikhote-Alin must be the rocks of the Dembi Suite, a constituent of the Kizinsky Formation (Group). Unfortunately, so far these rocks have been found only in scarce localities in the coastal zone of the Tatar Strait, between Cape Zolotoi and Cape Gydzhu and between Cape Datta and Cape Syurkum. The volcanic rocks of the Dembi Suite are basaltic andesites, andesites, and dacites. On the chemical basis they can be attributed to the calc-alkaline series. In the East Sikhote-Alin volcanic activity took place under subaerial continental conditions. Its products are identical to or resemble the Cenozoic volcanics of Mexico, of some states of Central America, and of some regions of the American Cordilleras and Andes.
Keywords: Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен